Characterization of Culex pipiens Complex (Diptera: Culicidae) Populations in Colorado, USA Using Microsatellites - Kothera, Linda (Public Library of Science, 2012)
Mosquitoes such as those in the Culex pipiens complex are important vectors of disease. This study was conducted to genetically characterize Cx. pipiens complex populations in the state of Colorado, USA, and to determine the number of genetic clusters represented by the data. Thirteen populations located among four major river basins were sampled (n = 597 individuals) using a panel of 14 microsatellites. The lowest-elevation sites had the highest Expected Heterozygosity (H(E)) values (range 0.54–0.65). AMOVA results indicated the presence of statistically significant amounts of variation within each level when populations were analyzed as one group or when they were grouped either by river basin or by their position on the east or west side of the Rocky Mountains. Most pairwise F(ST) values were significant via permutation test (range 0–0.10), with the highest values from comparisons with Lamar, in southeast CO. A neighbor joining tree based on Cavalli–Sforza and Edwards’s chord distances was consistent with the geographic locations of populations, as well as with the AMOVA results. There was a significant isolation by distance effect, and the cluster analysis resolved five groups. Individuals were also assayed with an additional microsatellite marker, Cxpq78, proposed to be monomorphic in Cx. pipiens but polymorphic in the closely related but biologically distinct species Cx. quinquefasciatus. Low frequencies (≤3%) of Cx. quinquefasciatus alleles for this marker were noted, and mostly confined to populations along the Interstate 25 corridor. Pueblo was distinct in that it had 10% Cx. quinquefasciatus alleles, mostly of one allele size. The degree of population genetic structure observed in this study is in contrast with that of Cx. tarsalis, the other major vector of WNV in the western U.S., and likely reflects the two species’ different dispersal strategies.